Do Primary Emotions Predict Psychopathological Symptoms? A Multigroup Path Analysis - Fuchshuber, Jürgen; Hiebler-Ragger, Michaela; Kresse, Adelheid; Kapfhammer, Hans-Peter; Unterrainer, Human Friedrich (Frontiers in Psychiatry, 2019)
Background: Research involving animal models has repeatedly proposed dysregulations in subcortically rooted affective systems as a crucial etiological factor in the development of a variety of psychiatric disorders. However, empirical studies with human participants testing these hypotheses have been sparse. Associations between primary emotions systems and different psychiatric symptoms were investigated in order to gain insights into the influence of evolutionary-rooted primary emotions on psychopathology. Material and Methods: The community sample included 616 adults (61.9% female). 243 reported a psychiatric lifetime diagnosis. By applying path analysis, we estimated paths between SEEKING, ANGER, FEAR, SADNESS, CARE and PLAY (Affective Neuroscience Personality Scales; ANPS) and symptoms of substance abuse (Alcohol, Smoking and Substance Involvement Screening Test; ASSIST) as well as depression, anxiety and somatization (Brief Symptom Inventory; BSI-18). To examine the moderator effects of gender and psychiatric lifetime diagnosis, multigroup analysis was applied. Results: Substance abuse was associated with male sex (β = -.25), SADNESS (β = .25) and ANGER (β = .10). Depression was associated with SADNESS (β = .53), FEAR (β = .10), SEEKING (β = -.10) and PLAY (β = -.15). Anxiety was linked to SADNESS (β = .33), FEAR (β = .21) and PLAY (β = -.10). Somatization was associated with SADNESS (β = .26) and PLAY (β = -.12; all p < .001). Multigroup analysis revealed no differences in paths between tested groups (all p > .01). The model explained 14% of the variance of substance abuse, 52% of depression, 32% of anxiety and 14% of somatization. Conclusions: The results further our understanding of the differential role of primary emotions in the development of psychopathology. In this, the general assumption that primary emotion functioning might be a valuable target in mental health care is underlined.